Sustainable certification in the Malaysian palm oil industry - Sean Andrew Labansing; Rini Suryati Sulong; Sidah Idris (Asian Scholars Network, 2021)
One of the recurring issues with managing sustainable development initiatives in developing countries lies in balancing the economic development needs of a country whilst striving to avoid environmental degradation. Although economic growth is a priority for most countries, uncurbed development can lead to environmental degradation which can have a long lasting negative impact on society as a whole. Hence, the need to balance development and environmental protection for the common good has fueled the call for greater commitment towards sustainable development initiatives for countries with heavy reliance on the agriculture sector. One of the most debated issues of sustainable development relates to the palm oil industry. In this paper, we will look at how the concept of sustainable development has been translated in sustaining the palm oil industry. Given the pivotal role that sustainable certification plays in the palm oil market, it is crucial to establish whether or not the sustainable certification of the palm oil industry is warranted. Through this paper, we argue that a clear understanding of the palm oil industry’s business ecosystem is needed, because for sustainability initiatives to succeed, all parties in the ecosystem must have a clear understanding of sustainability.